Thy1 is a positive regulator of osteoblast differentiation and modulates bone homeostasis in obese mice. Issue 6 (17th January 2018) - Paine, Ananta; Woeller, Collynn F.; Zhang, Hengwei; de la Luz Garcia-Hernandez, Maria; Huertas, Nelson; Xing, Lianping; Phipps, Richard P.; Ritchlin, Christopher T.
ABSTRACT: Thy1 (CD90), a glycosylated, glycophosphatidylinositol‐anchored membrane protein highly expressed by subsets of mesenchymal stem cells and fibroblasts, inhibits adipogenesis. The role of Thy1 on bone structure and function has been poorly studied and represents a major knowledge gap. Therefore, we analyzed the long bones of wild‐type (WT) and Thy1 knockout (KO) mice with micro‐computed tomography (micro‐CT) and histomorphometry to compare changes in bone architecture and overall bone structure. micro‐CT analysis of long bones revealed Thy1 KO and WT mice fed a high‐fat diet demonstrated bone structural parameters at 4 mo that differed significantly between WT and KO mice. A significant reduction in trabecular bone volume was noted in Thy1 KO mice. The most prominent differences were observed in trabecular bone volume ratio and trabecular bone connectivity density. Consistent with micro‐CT measurements, histomorphometric analysis also showed decreased bone volume in the obese Thy1 KO mice compared to obese WT mice. In vitro assays revealed that osteogenic conditions increased Thy1 expression during OB differentiation and absence of Thy1 attenuated osteoblastogenesis. Together, these findings support the concept that Thy1 serves as a major mechanistic link to regulate bone formation and negatively regulate adipogenesis.—Paine, A., Woeller, C. F., Zhang, H., Garcia‐Hernandez, M. L., Huertas, N., Xing, L., Phipps, R. P., Ritchlin, C. T. Thy1 is a positive regulator of osteoblast differentiation and modulates bone homeostasis in obese mice. FASEB J. 32, 3174–3183 (2018). www.fasebj.org